PENGARUH PENGGUNAAN FILTER UDARA VARIASI TERHADAP DAYA, TORSI, DAN EFISIENSI KONSUMSI BAHAN BAKAR PADA SEPEDA MOTOR HONDA BEAT - Rahmat Rivais; Nuzul Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study aimed to determine the effect of using a modified air filter set consisting of a stainless steel air filter and a slim filter box on the power, torque, and fuel consumption efficiency of a 2019 Honda Beat motorcycle. The study was motivated by the widespread use of aftermarket air filters that are claimed to improve engine performance and fuel efficiency; however, these claims have not been sufficiently supported by measurable experimental data.This research employed an experimental method using a Posttest-Only Control Design. Testing was conducted on a 2019 Honda Beat motorcycle using a chassis dynamometer to measure engine power and torque, while fuel consumption was measured using a burette at engine speeds ranging from 1,700 to 4,000 rpm over a 90-second testing period. The collected data were analyzed using mean calculations and percentage increases or decreases in the test results.The results showed that the modified air filter set increased the average engine power by 15.57%, with improvements of 6.17% at 6,000 rpm, 21.74% at 7,800 rpm, and 18.79% at 9,300 rpm. Engine torque also increased by an average of 15.50%, consisting of 6.34% at 6,000 rpm, 21.59% at 7,800 rpm, and 18.56% at 9,300 rpm. In addition, the modified air filter set reduced average fuel consumption by 5.48%, with the greatest reduction of 8.50% recorded at 4,000 rpm. Based on these findings, it can be concluded that the use of a modified air filter set, consisting of a stainless steel air filter and a slim filter box, has a positive effect on the performance of the 2019 Honda Beat motorcycle by increasing engine power and torque while improving fuel consumption efficiency.